Incidence, clinical features and diagnosis of cicatrising conjunctivitis in Australia and New Zealand. (October 2018) - Bobba, Samantha; Devlin, Connor; Di Girolamo, Nick; Wakefield, Denis; McCluskey, Peter; Chan, Elsie; Daniell, Mark; Watson, Stephanie
Abstract Aims This study aimed to determine the incidence, clinical features and management of cicatrising conjunctivitis in Australia and New Zealand, also enabling comparison with data from the United Kingdom. Methods A prospective surveillance study was conducted over 17 months via the Australian and New Zealand Ophthalmic Surveillance Unit with a one-year follow-up period. Practicing ophthalmologists on the Surveillance Unit's database were asked to report recently diagnosed cases of cicatrising conjunctivitis on a monthly basis. Initial and follow-up questionnaires were sent to ophthalmologists who had reported positive cases to obtain demographic and clinical data. The minimum incidence of cicatrising conjunctivitis was calculated based on cases reported during the study period and from population data. Results During the 17-month study period (December 2011–April 2013), 56 cases of cicatrising conjunctivitis were reported. Data was obtained for 35 cases (62%) with a mean age of 74 years (range, 28–94 years). The most common aetiologies were ocular mucus membrane pemphigoid (n = 18 cases, 51.4%), Stevens–Johnson Syndrome (n = 3, 8.6%) and graft versus host disease (n = 3, 8.6%). The minimum incidence of cicatrising conjunctivitis in Australia and New Zealand was 1.5 per million, comparable to incidence data from the United Kingdom. Conclusions This study is the first to prospectively record the incidence of cicatrising conjunctivitis in Australia and New Zealand and the second worldwide. It provides novel data on demographics and management of cicatrising conjunctivitis, as reported by treating ophthalmologists.